2016
DOI: 10.1021/acs.orglett.6b01560
|View full text |Cite
|
Sign up to set email alerts
|

A Series of β-Carboline Alkaloids from the Seeds of Peganum harmala Show G-Quadruplex Interactions

Abstract: In this study, we screened 17 medicinal plants for binding activity to G-quadruplex d(TTGGGTT)4 by (1)H NMR spectroscopy and found that the crude extract of Peganum harmala L. seeds showed the most potential binding activity. Subsequently, (1)H NMR- and bioassay-guided isolation of the extract of P. harmala L. was performed to obtain four pairs of partially racemized β-carboline alkaloids, pegaharmines A-D (1-4). Their structures and absolute configurations were determined by extensive NMR analyses, X-ray crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Our previous study revealed that alkaloids from M . cordata exhibited promising antiproliferative effects, so all the isolated compounds were tested for the growth inhibitory activities against HL-60, A-549, MCF-7 human cancer cell lines by the trypan blue method and MTT method 9 , 10 . The results were summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study revealed that alkaloids from M . cordata exhibited promising antiproliferative effects, so all the isolated compounds were tested for the growth inhibitory activities against HL-60, A-549, MCF-7 human cancer cell lines by the trypan blue method and MTT method 9 , 10 . The results were summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…β-carboline alkaloids lead to the formation of G-quadruplexes which consist of four guanine bases assembling in a three-dimensional square planar structure. These arrangements play regulatory roles on genes, most importantly on oncogenes, thus acting as antitumor agents against human promyelocytic leukemia, prostate cancer, and gastric cancer [ 46 , 78 , 79 ]. The formation of G-quadruplexes can be considered as a novel approach for cancer treatment and can have promising applications in anticancer drug design.…”
Section: Emerging Cytotoxic Alkaloids: Apoptotic Strategmentioning
confidence: 99%
“…Article Related Abbreviations: EIC, extracted ion chromatogram; FA, formic acid human cancer cell lines [6]. Four pairs of partially racemized beta-carboline alkaloids with rare carbon skeleton from Peganum harmala L. seeds showed the strongest Gquadruplex interaction and exhibited significant cytotoxic activity against three cancer cell lines [7]. Therefore, the purification and pharmacological study of different alkaloids especially trace alkaloids are of great significance.…”
Section: Introductionmentioning
confidence: 99%